2016
DOI: 10.1007/s13538-016-0474-8
|View full text |Cite
|
Sign up to set email alerts
|

Properties of Atmospheric Pressure Ar Plasma Jet Depending on Treated Dielectric Material

Abstract: Atmospheric pressure plasma jet operated in argon was utilized to modify surfaces of glass, acrylic, and PTFE dielectrics. This paper describes the influence of the dielectric substrate on operation and properties of plasma. Two modes of operation (each of those have two patterns) were described. The transition from one mode to another, values of the dissipated power, and spreading of plasma over the dielectric surfaces strongly depended on the substrate material. Additionally, three methods of plasma spreadin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 28 publications
0
10
0
Order By: Relevance
“…Works concerning interactions of Ar APPJs with dielectric targets (grounded or not) are also available in the literature [19][20][21][22][23][24][55][56][57]. Most of them, though, use AC waveforms (kHz-MHz frequency range) for plasma generation, and the APPJ characterization is done by means of voltage-current, timeintegrated imaging, and emission spectroscopy methods [19][20][21][22]56,57]. Only few works, also using AC power supplies, have combined the previous experimental methods with ICCD imaging for similar studies [23,24,55].…”
Section: Ir and Iccd Imagingmentioning
confidence: 99%
“…Works concerning interactions of Ar APPJs with dielectric targets (grounded or not) are also available in the literature [19][20][21][22][23][24][55][56][57]. Most of them, though, use AC waveforms (kHz-MHz frequency range) for plasma generation, and the APPJ characterization is done by means of voltage-current, timeintegrated imaging, and emission spectroscopy methods [19][20][21][22]56,57]. Only few works, also using AC power supplies, have combined the previous experimental methods with ICCD imaging for similar studies [23,24,55].…”
Section: Ir and Iccd Imagingmentioning
confidence: 99%
“…The presence of a target also increases the He metastable density [7,8]. When interacting with low-permittivity targets surface ionization waves are initiated and their speed, morphology, radius of spreading and surface charging depend on the electrical properties of the target [9][10][11][12][13]. Highpermittivity and metallic targets can induce a return stroke (also referred to as restrike, rebound, reflected ionization wave or backwards ionization wave) instead [10,[14][15][16][17][18].…”
Section: Introductionmentioning
confidence: 99%
“…To generate APPJs most of them use sinusoidal voltages, ranging in frequencies from kHz to MHz. Previous works of our groups revealed that using conducting or dielectric targets (or sample holders) has important effect not only on plasma jet properties but also on plasma treatment outcome [11,17]. For instance it was verified that better adhesion of polydimethylsiloxane (PDMS) samples were achieved after plasma treatment using a conductive sample holder [17].…”
Section: Introductionmentioning
confidence: 91%
“…Studies regarding the interaction between APPJs and different substrates have shown that the target conductivity is a key parameter that influences not only the treatment results, but can also modify the characteristics of the plasma jet itself [11,12,13,14]. Works concerning differences in plasma jet properties when impinging on grounded or floating targets have been reported [15,16].…”
Section: Introductionmentioning
confidence: 99%